Male participation in selected areas of reproductive health and the effectiveness of a male-focused, occupational-based intervention in Kalutara - Jayasekera, C (My University, 2011)
The objective of this study was to assess the knowledge, opinion and participation among married, employed males in the areas of household chores (HHC), contraception and child bearing. The study was conducted in the Kalutara educational zone, among 440 married men in 47 workplaces using stratified cluster sampling technique. Men's knowledge and opinion were assessed using a self-administered questionnaire. Their participation was assesses one month before assessing the knowledge and opinion, by interviewing the wives at their residences. A weighted score developed by a group of experts was used to quantity the findings. The intervention was using a quasi-experimental study design (randomization was not performed) in which an IEC programme was given to males in the study group at their workplaces by PHI while the control group did not receive any intervention. The postintervention assessment was carried out six months after the intervention. There were no significant differences between study and control groups at the pre-intervention baseline assessment. The effectiveness of the intervention was assessed by comparing the pre- and post-intervention scores. After the intervention, there was a significant improvement in the mean scores of knowledge and opinions in HHC, contraception and child rearing between the post- and pre-intervention scores in the study group, while the control group did not show a significant improvement. In participation in HHC, a significant improvement was observed in the study group, while the control group did not show a significant improvement in the scores between post- and pre-intervention assessments. These results clearly demonstrate the effectiveness of the IEC package implemented by PHII in improving the knowledge and favourable opinions of males in HHC, contraception and child rearing and, participation in HHC